A modified technique of Duhamel procedure for the treatment of Hirschsprung disease ( anastomosis without suturing). - ناصر, محمد (Latakia University Journal -Medical Sciences Series, 2021)
Back ground/ purpose: the aim of this study was to evaluate the long- term follow-up results of a modified technique of Duhamel operation for the treatment of Hirschsprung disease in 32 pediatric patients admitted in Al Assad and Tishreen university hospitals-department of pediatric surgery in lattakia-Syria,between the year of 2005- 2020 Materials and Methods: 32 pediatric patients with rectal and sigmoid aganglionosis have been operated by modified technique of Duhamel operation for HD, divided in three groups: Group I: 4 patients operated by 3 stage procedure Group II: 8 patients operated by two stage procedure Group III: 20 patients operated by one stage procedure without colostomy The modified technique is by using a special crushing clamp, which is placed on the posterior aganglionic wall of the rectum and anterior wall of ganglionic one of the normal colon after pull-through for fixation without suturing or utilizing any stapler. The clamp will fell down after 5-7 days by aseptic necrosis, and a wide side-to- side anastomosis is completed Results: Early postoperative complications were seen in four patients as minimal fecal soiling (one in group I, 1 in group II and two in group III respectively) which was disappeared after one month spontaneously. Functional results in all patients were good in 28 patients (87.5%), constipation was in two patients (6.25%), which controlled with high-fiber diet and an oral laxative. Conclusion: this modified technique of Duhamel procedure is safe and easy performable with good results.